Organ transplantation through historical and religious aspects with reference to Montenegro - Peličić Damir N. (Hospital Pharmacology)
Introduction: Since the second half of the twentieth century, thousands of human lives have been saved worldwide by organ transplantation. Montenegro is one of the signatories of the Istanbul Declaration, which strictly prohibits the trade in human organs. In 2009, a law was adopted in Montenegro that allows organ transplantation for medical purposes, which is in accordance with European and international legislation. Methods: For this paper, we conducted a systematic literature search using relevant historical religious, ethical, and medical data. We searched databases: Pubmed, Scopus, EB-SCO, Google scholar, Serbian citation index, Researchgate and others. We also referred to the experiences gained in the work at the Clinic for Nephrology of the Clinical Center of Montenegro. The keywords we used for the literature search were related to: History of Medicine, Ethics, Monotheistic Religions, Transplantation Program and Legislation in Biomedicine. Topic: Organ transplantation is a method over 70 years old; its general application has been delayed due to the inevitable rejection of the transplanted organ. Organ transplantation is one of the most significant scientific discoveries in surgery and immunology and is significant for the therapeutic progress of modern medicine. Conclusion: This is a complex topic that requires extensive information, not only in the medical field of research, but also in the legal, ethical and religious fields. Evidence-based medical guidelines, ethical, religious aspects, the Istanbul Declaration, and careful consideration must be taken into account before making a decision that is best for the patient, his family, and the country's health care system.